2018
DOI: 10.1016/j.jor.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Total shoulder arthroplasty in octogenarians: Is there a higher risk of adverse outcomes?

Abstract: This study used the National Surgical Quality Improvement Program to evaluate octogenarians who underwent total shoulder arthroplasty (TSA). Specifically, we evaluated: (1) patient demographics; (2) perioperative factors; and (3) 30-day postoperative complications. Compared to controls, the octogenarians had more females, white patients, lower BMIs, fewer smokers, less functionally independent, higher ASA scores, shorter operative times, and longer LOS. Octogenarians had greater odds for developing any (OR = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… 39 Studies that do present risk estimates at 30 and 90 days post-surgery are typically limited by small sample size and again are skewed by the inclusion of trauma and revision procedures. 40 41 42 We did not include additional estimates of symptomatic deep vein thrombosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Studies that do present risk estimates at 30 and 90 days post-surgery are typically limited by small sample size and again are skewed by the inclusion of trauma and revision procedures. 40 41 42 We did not include additional estimates of symptomatic deep vein thrombosis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One study similarly found a higher overall complication rate in octogenarians. However, this group also found that octogenarians were at a higher risk of several, specific major and minor complications within 30 days including pulmonary embolism, stroke, myocardial infarction, reintubation and septic shock [ 11 ]. The differences between our results and the aforementioned study are likely due to the fact that the aforementioned study did not create two equal sized groups, but rather compared all TSA patients in the database for a set time period.…”
Section: Discussionmentioning
confidence: 99%
“…Age has often been identified as a risk factor for complication throughout the orthopaedic literature [11][12][13][14]. However, this risk factor is non-modifiable, and with an aging population in the United States, there is a need for surgeons to better understand the impact of age on orthopaedic outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations